Using adaptability principles in developing chassis for transport and road construction machines - Dobretsov Roman; Shen Yunfeng; Karnaukhov Andrey; Malyukova Margarita; Sabitov Linar; Kiyamov Ilgam; Taraban Maria (E3S Web of Conferences)
The article considers the approach to determining the structure of a high-cross-country chassis and the principles of calculating its main weight, size and energy parameters. The relevance of the problem is determined by the lack of Russian developments in the field of creating chassis for road construction machines suitable for work in difficult terrain. The need for such chassis is determined by the need to ensure the implementation of operational work in difficult landscape conditions and areas of natural and man-made disasters. The proposed chassis weighing 11 ... 13 tons is articulated, three-section. The energy source is a heat engine (diesel is considered as a basic solution). It is proposed to use the principle of parallel electromechanical transmission, in which traction electric motors, controlled power distribution mechanisms, and step-down wheel reducers are installed on two sections. Steering is controlled by the onboard principle. The mover in the basic version is wheeled. On soft soils, it is proposed to use triangular track modules for the front and middle sections. The rear section is equipped with two driving axles and removable tracks can be installed on the side wheels.